Method of Sharing Marriage Properties in the Religious Court, Palu - Moh. Thariq Godal; Syarif Hasyim; Musyahidah Musyahidah (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2020)
The aim of this paper is to discusses Marriage properties method sharing in the Religious Court of Palu City. This study uses qualitative methods and data was gathered through observation, in-depth interviews, and written material. Data analysis was analyzed using grounded theory approach. The results of this study indicate that terminating the distribution of marital assets is sufficient to provide justice for the plaintiffs and defendants. Joint assets are divided in half for each party if under normal conditions, namely the husband provides support for the family and the wife takes care of the household. The division of joint assets based on contributions in marriage is one of the considerations by the judge in deciding joint property cases. This means that the sharing of joint assets does not refer to Article 97 of the Compilation of Islamic Law, namely that joint assets are divided in two for each party, but divided by 2/3 for the wife and 1/3 for the husband in certain cases (casuistik). Judges in the decision on the distribution of joint assets are still based on legal principles and norms.